2002
DOI: 10.1046/j.1469-0691.2002.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Malassezia species from patient skin scales by PCR-RFLP

Abstract: The proposed method, described for the first time, could provide a sensitive and rapid detection and identification system for Malassezia species, which may be applied to epidemiological surveys and routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 26 publications
4
63
0
12
Order By: Relevance
“…Several findings from this study are consistent with those previously reported by Sugita et al (45) and Gaitanis et al (19). The results of these studies are expected to be free of potential culture bias.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several findings from this study are consistent with those previously reported by Sugita et al (45) and Gaitanis et al (19). The results of these studies are expected to be free of potential culture bias.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, all of the methods mentioned above (except denaturing gradient gel electrophoresis) require cultivation to enhance sensitivity, thereby increasing both the potential for culture bias and the turnaround time for analysis. Two methods have been reported to differentiate complex Malassezia communities from skin without cultivation (19,27,45), but these methods require either separate amplification with specific primer sets for each species or restriction digestion. The terminal fragment length polymorphism (tFLP) method uses only three different primer sets, minimizing the potential bias related to amplification efficiency.…”
mentioning
confidence: 99%
“…To overcome the limits of morphological assessment, recent studies have used a variety of molecular methods such as the nested polymerase chain reaction (PCR) 12 , real-time PCR 13 , pulsed field gel electrophoresis (PFGE) 14 , amplified fragment length polymorphism (AFLP) 15,16 , denaturing gradient gel electrophoresis (DGGE) 16 , random amplification of polymorphic DNA (RAPD) 16,17 , single strand conformation polymorphism (SSCP) 18 , terminal fragment length polymorphism (tFLP) 19 , restriction fragment length polymorphism (RFLP) [20][21][22][23] , and sequencing analysis 24 .…”
Section: Introductionmentioning
confidence: 99%
“…This phenotypic system has been used as the conventional method of identification, though in practice, the test results are not always easy to read. Therefore, several research groups have explored the use of molecular techniques, such as pulsed-field gel electrophoresis (3, 4, 36), randomly amplified polymorphic DNA analysis (1, 3), amplified fragment length polymorphism (AFLP) analysis (40), denaturing gradient gel electrophoresis (40), multilocus enzyme electrophoresis (30), sequencing analysis (37), restriction analysis of PCR amplicons of ribosomal sequences (8,15,16,20,28), and chitin synthase gene sequence analysis (1,4,8,37), for the identification of Malassezia species. Recently, Gemmer et al (9) devised a remarkably efficient, novel technique, terminal fragment length polymorphism analysis, for the rapid and reliable identification of Malassezia species.…”
mentioning
confidence: 99%